The diversity of birds and frogs species at Perdana Botanical lake Garden Kuala Lumpur - Baharuddin, Zainul Mukrim; Rusli, Nadia; Ramli, Lukman; Othman, Rashidi; Yaman, Maheran (2016)
Unbalance urban development would affect the ecosystem and environment of the people and living things. Declining and loss of flora and fauna species occurs because of landscapes and living habitat changes. Urban biodiversity is a part of ecological elements and ecosystems services of the urban environments. Thus, it is important to be maintained or preserved in urban planning and design. The lack numbers of study focusing on the field of urban wildlife such as birds and frogs around the globe. Thus, the aim of the study is to understand the scientific data on urban wildlife mainly focus on birds and amphibian. This study willprovide significant information pertaining to urban biodiversity issues. Birds are chosen as the best example that will act as an indicator for the inland environment while frogs as the amphibian for the urban lake garden. Birds can be the best indicator for inland environment while frogs can be the indicator for the aquatic environment of the urban lake garden. The study was conducted at Perdana Botanical Lake Garden in Kuala Lumpur, Malaysia. The observation survey includes in details of the name of the species, number of species, habitat, data observation on time and dates, remarks and reference notes. The survey method on birds used the transect lines in order to observe the bird species within a measured line. The observervationincludes calculations and records of all the birds species, while walking along the transect route at average speed of 15m/min within 30m distance. The survey usually conducted either early in the morning and late evening. Meanwhile, the amphibian observation on frogs survey basedon ‘Quadrant Sampling’ which is the standard quadrant being set in metre (m), in which 5 x 5 m and 10 x 10 m. The amphibian observation begin duringthe night time for 3 days duration started from 7.00 pm to 9.00 pm. Based on the observation at Botanical Perdana Garden, 8 species of birds have been identified. The most common is Acridotheres Tritis /Common Myna (n=19) and the least is Geopelia Strata /Zebra Dove shows (n=1).During the observation, a total of 6 species of frogs was found. The highest species of frogs recorded were Hylarana erythraea /Green Paddy Frog with (n=80), while Fejervarya limnocharis. /Indian Rice Frog (n=1). The result concludes that the park needs to have more species of birds that share the sameeating diet such as frugivorous and nectarous. The lake garden should restructured especially the pond with ecological approach to attract more typesof frogs.